الأسس التصميمية للحدائق العامة وساحات اللعب لتلبي حاجات الأطفال المعاقين حركياً - محمود سلمان; خضرة سجا (Latakia University Journal -Engineering Sciences Series, 2016)
إنّ عملية دمج الأطفال المعاقين حركياً في المجتمع من خلال التأهيل النفسي والاجتماعي لا تكفي ، بل يجب دمجهم مع البيئة الخارجية التي يعيشون فيها من خلال تكييف التصاميم المعمارية والعمرانية لتناسب إمكانياتهم الخاصة . و تعتبر الحدائق وساحات اللعب من أهم عناصر البيئة الخارجية بالنسبة إلى الأطفال التي يمكن أن تعزز عملية الدمج من خلال تأمين الفرص المناسبة للمشاركة في اللعب مع الأطفال العاديين . يقدم البحث دراسة تحليلية لبعض الحدائق العامة في مدينة دمشق بهدف التحقق من مدى تلبية عناصرها المعمارية لحاجات الأطفال المعاقين حركياً من حيث سهولة الوصول وإمكانية استخدام أجهزة اللعب ، وذلك من خلال تحليل العناصر التصميمية للحدائق المدروسة وتقييمها وفق المعايير الموصى بها .وتبين بنتيجة الدراسة أنّ العناصر التصميمية للحدائق المدروسة لم تراع الأسس والمعايير الموصى بها لتحقيق حاجات المعاقين حركياً . The process of integrating motor disability children is not done just by psychological and social rehabilitation, but it must integrate them with the outdoor environments in which they live, adapting the architectural and urban designs to be convenient with their own abilities.Gardens and playgrounds considered one of the most important outdoor environments for children; it can help in integration by providing suitable opportunities to participate in playing with ordinary children. The research includes an analytical study of some public gardens in Damascus in order to verify the architectural elements for motor disability needs, by accessibility and usability of playgrounds equipment, by analyzing the design elements of the case studied and evaluating them according to the norms are well recommended. The research concluded that the design elements of the case studied did not take into account the principles and norms whichare well recommended to achieve the motor disability needs.